Efektifitas Komunikasi Interpersonal Sales Staff Dalam Menerapkan Standar Pelayanan Sukses - Danny Jonathan Sitompul; Effiati Juliana Hasibuan; Rehia K. Isabela Barus (Universitas Medan Area, 2021)
Interpersonal communication is needed in retail. Salesperson Activity can not be separated from communication with consumers. This study describes how the interpersonal communication of salesperson in applying SUKSES service standards in Sports Station Medan Mall. This study aims to determine the effectiveness of salesperson interpersonal communication in implementing SUKSES service standards. This study used a qualitative approach in which the source of data is four of Sports Station Medan Mall salesperson, one supervisor and two customers. Data collected through direct observation in the store, in - depth interviews with sources and literature. Proceed with interactive data analysis techniques starting from data reduction, data display, and conclusion drawing/ verificaton. From these results it can be seen that, the role of interpersonal communication is very important in the implementation of SUKSES service standards. The results of this research are we can know how the way they communicate, that is greet customer, customer approach, analyzing the needs of consumers, merchandise offers, and to thank and invite customers to come back. Interpersonal communication adopted by the salesperson is not only verbal, but also nonverbal.